Designing agroforestry cacao to implement multifunctional landscapes by synergizing ecosystem service and economic value1 - Yudha Kristanto; Suria Tarigan; Tania June; Bambang Sulistyantara; Pini Wijayanti (Trees, Forests and People)
Heightened awareness of monoculture cacao's negative impacts has led to the adoption of multifunctional landscape approaches aimed at optimizing ecological, social, and economic outcomes in cacao plantations. This study outlines multifunctional landscape plans for the Rongkong watershed, addressing both land and landscape scales to support sustainable and regenerative cacao development. The landscape planning includes agroforestry-based land-sharing scenarios and land-sparing approaches, evaluated based on the synergy and economic value of ecosystem services provided. The cacao-durian-avocado agroforestry combination stands out as the most advantageous, offering synergistic benefits in provisioning and regulating services, along with substantial financial gains. This scenario yields higher values for FNPV, ENPV, FBCR, and EBCR, achieving up to 2.23, 1.66, 1.77, and 1.51 times the value of monoculture cacao in upstream areas, and 2.26, 1.61, 1.78, and 1.42 times in downstream regions. Additionally, managing this combination through land-sparing methods allows 0.4 ha per ha of agricultural farm to be saved while delivering equivalent benefits. At a broader landscape level, the cacao-durian-avocado model is promising when scaled to replace monoculture cacao, traditional agroforestry, and marginal lands. Nevertheless, it's essential to recognize that variations in biophysical and socioeconomic conditions can influence differences in land equivalent ratio (LER), net present value (NPV), and benefit-cost ratio (BCR) across multifunctional landscapes.